Kepala Sekolah Sebagai Manajer dalam Meningkatkan Profesionalisme Guru Pendidikan Agama Katolik di SDK Botung - Magdalena Wola, Maria; Petrus Tukan; Vinsensius Bawa Toron (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study focuses on the role of the principal as a manager in professionalism of Catholic Religious Education teachers at SDK Botung. The aim is to determine the extent of the principal’s role as a manager in improving the professionalism of Catholic Religious Education teachers through. The study used a descriptive qualitative method. This study was conducted at SDK Botung, invoving 3 research subjects consisting of the principal and 2 Catholic Religious Education teachers. Data were collected through interviews, observations and documentation, then analyzed using data reducation techniques, data presentation and drawing conclusions. The results of the study indicate that the principal has not fully carried out his role as a manager. So it is necessary to improve the profession of Catholic Religious Education teachers.